Design and Operation of Mini-TEA CO2 Laser and Investigation of Preionization Effect - Haider, Adawiya J.; Hamza, Falih H. (Iraqi Journal of Laser, 2005)
A Mini-TEA CO2 laser system was designed and operated to obtain a pulse at 10.6 μm. Output energy of 30 mJ, with preionization pins, and pulse duration of 100ns were obtained. While an output energy of 6mJ and pulse duration of 100 ns in absence of pre-ionization were obtained. The system was operated with Ernest profile main-discharge electrodes. Dependencies of supply voltage and output laser energy on the pressure inside laser cavity were investigated as well as dependencies of supply voltage and output energy on the main capacitor(8CO2 : 8N2 : 82He :2CO). Efficiency of was calculated to be 4.4%.